General notes on ductility in timber structures - Jorissen, André; Fragiacomo, Massimo (Engineering structures, 2011)
The paper discusses the implications of ductility in design of timber structures under static and dynamic loading including earthquakes. Timber is a material inherently brittle in bending and in tension, unless reinforced adequately. However connections between timber members can exhibit significant ductility, if designed and detailed properly to avoid splitting. Hence it is possible to construct statically indeterminate systems made of brittle timber members connected with ductile connections that behave in a ductile fashion. The brittle members, however, must be designed for the overstrength related to the strength of the ductile connections to ensure the ductile failure mechanism will take place before the failure of the brittle members. The overstrength ratio, defined as the ratio between the 95th percentile of the connection strength distribution and the analytical prediction of the characteristic connection strength, was calculated for multiple doweled connections loaded parallel to the grain based on the results of an extensive experimental programme carried out on timber splice connections with 10.65 and 11.75 mm diameter steel dowels grade 4.6. In this particular case the overstrength ratio was found to range from 1.2 to 2.1, and a value of 1.6 is recommended for ductile design. The paper illustrates the use of the elastic–perfectly plastic analysis with ductility control for a simple statically indeterminate structure and compares this approach to the fully non-linear analysis and with the more traditional linear elastic analysis. It is highlighted that plastic design should not be used for timber bridges since fatigue may lead to significant damage accumulation in the connections if plastic deformations have developed. The paper also shows that the current relative definitions of ductility, as a ratio between an ultimate deformation/displacement and the corresponding yield quantity, should be replaced by absolute definitions of ductility, for example the ultimate deformation/displacement, as the latter ones better represent the ductile structural behavior. ► Ductility in timber structures can be achieved mainly by designing ductile connections. ► Timber members, however, must be designed for the overstrength of the connections. ► Overstrength is the ratio between the 95th percentile and the analytical design strength. ► An overstrength ratio of 1.6 is recommended for doweled timber splice connections. ► Absolute definitions like the ultimate deformation should be used to measure ductility.